PENGARUH PELAKSANAAN ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) TERHADAP KINERJA KEUANGAN PERUSAHAAN DI INDONESIA - Dequelju, Agnes (MANAJEMEN DEWANTARA, 2024)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) implementation on the financial performance of companies in Indonesia during the 2020–2022 period. The research uses a quantitative approach with purposive sampling to select 46 companies listed on the Indonesia Stock Exchange (IDX) that have adopted ESG practices. The data is analyzed using multiple linear regression with Return on Assets (ROA) as the dependent variable, alongside ESG scores and control variables such as leverage, firm size, liquidity, and company growth. The results show that ESG practices, particularly environmental performance, have a significant positive impact on financial performance. However, social and governance scores do not show a significant effect. Additionally, firm size positively affects financial performance, while leverage and company growth have significant negative impacts. These findings highlight the importance of integrating environmental factors to improve financial outcomes and long-term sustainability in Indonesia.